Refugees Insertion and Labor Market Outcomes and: An Analysis of the Egyptian Context - Ebrahim, Salma (AUC Knowledge Fountain, 2024)
This thesis examines the association between the inflow of refugees to Egypt and labor market outcomes during the period 2012-2018, using data from the Egyptian Labor Market Panel Survey (ELMPS). By applying Difference-in Differences and Probit models, the study compares labor market outcomes between Greater Cairo, characterized by high refugee inflow, and the Suez Canal region, which has a very low inflow. The labor force outcomes analyzed wages, formality and labor force participation. The results indicate that the refugee influx is associated with a decline in wages for both formal and informal workers in the treatment group compared to the control group. On the contrary, the results suggest that individuals in the treatment region had a higher probability of participating in the labor force relative to individuals in the control group. Finally, no significant association was found between the refugee influx and the formality of employment. This study contributes to the literature by providing empirical evidence on the labor market effects associated with demographic shifts due to refugee inflows in Egypt, an area that remains underexplored in migration studies despite its geopolitical and socio-economic significance in the MENA region.